KEBERADAAN DAN EKSISTENSI LOKALISASI PEKERJA SEKS KOMERSIAL - Titik Suharti (Perspektif, 2007)
Localization worker of commercial sex represent one of the negative influence minimization effort of deed digress conducted by some of is small of society. Pro and contra in discussing localization worker of commercial sex. Indonesia as Body Politic, arranging that localization worker of commercial sex is crime. But and existence of existence localization worker of commercial sex in the middle of society relied on made by discipline statement is or owner of pengelola and known by local Muspika, so that can be concluded that domiciling discipline statement oppose against law and regulation.